IbM KELOMPOK PUPUK KOMPOS PEMUDA MANDIRI DI DESA BENGKEL KECAMATAN LABUAPI KABUPATEN LOMBOK BARAT - Irianto, Irianto; Amrul, Rusli (Sekolah Tinggi Ilmu Ekonomi AMM Mataram, 2017)
Science and Technology Program for Communities (IbM) Workshop held in village districts Labuapi West Lombok district, in cooperation with two business partners namely the compost